2010
DOI: 10.1186/1471-2458-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the facilitators and barriers of antiretroviral adherence in Peru: A qualitative study

Abstract: BackgroundAntiretroviral scale-up is increasing in resource-constrained settings. To date, few studies have explored the barriers and facilitators of adherence to ART in these settings. Facilitators and barriers of antiretroviral adherence in Peru are not completely understood.MethodsAt two clinics that serve a large number of HIV-positive individuals in Lima, Peru, 31 in-depth interviews were carried out in 2006 with adult HIV-positive individuals receiving ART. Purposive sampling was used to recruit the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 35 publications
2
69
2
Order By: Relevance
“…Unlike a recent report conferring benefit among HIV-infected Peruvian men without assessment of alcohol or drug use [84], various reminders did not significantly influence ART adherence in our sample. Though not shown, those with AUDs were no more likely to use medication reminders than those without them.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Unlike a recent report conferring benefit among HIV-infected Peruvian men without assessment of alcohol or drug use [84], various reminders did not significantly influence ART adherence in our sample. Though not shown, those with AUDs were no more likely to use medication reminders than those without them.…”
Section: Discussioncontrasting
confidence: 95%
“…In our analyses, we did not explore in detail the impact of various types of stigma on ART adherence, but it is seductive to speculate that those who do not disclose their HIV status to others continually live in fear and miss doses based on concerns about someone finding out about their HIV status – as shown by previous studies conducted in Peru [84]. Further inquiry into various types of stigma is crucial for intervention development, especially with regard to HIV disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…27 Prior work in Lima found that fear of stigma or unwanted disclosure was a key barrier to adherence among PLWHA. 28 …”
Section: Study Settingmentioning
confidence: 99%
“…20 Barriers to MA were equally diverse and included patient factors (simply forgetting to take pills, fear of stigma, high cost of therapy), negative beliefs about medication (side effects, medications are harmful or ineffective), difficult medication schedule (dietary requirements with some pills, being away from home, being too busy) and other factors (mistrust in providers, feeling healthy, feeling hopeless, pill size, continued substance abuse).…”
Section: Barriers and Facilitators To Mamentioning
confidence: 99%
“…Participants in the study by Curioso et al stated they had a positive relationship with their providers that promoted MA while the participants in the study by Wayson-Locher et al stated that a lack of trust in their providers had a negative impact on MA. 18,20 Consequently, the concept of "trust" can be placed into both the facilitator and barrier categories depending on the perspective used in the original study.…”
Section: Structure Agency Facilitators and Barriersmentioning
confidence: 99%